Factors Affecting The Implementation of Balanced Nutrition in Toddlers in Sisumut Village, Kotapinang District, Labuhan Batu Selatan Regency - Hasnan Hajar; Muhammad Badiran; Asriwati; Dr. Anto J. Hadi, SKM, M.Kes, M.M (PT Yapindo Jaya Abadi, 2025)
Background: Nutritional problems are issues that occur throughout every stage of life, starting from the womb (fetus), infancy, childhood, adulthood, to old age. The aim of this study was to analyze the factors influencing the application of nutrition-conscious principles at the household level on the nutritional status of children under five. Methods: This research was an analytic survey with a cross-sectional study design. The study was conducted in Sisumut Village, Kota Pinang Subdistrict, South Labuhan Batu Regency, using a total sampling technique involving 50 mothers with children under five. Data were analyzed using chi-square and logistic regression tests. Results: The study found that the application of balanced nutrition was influenced by knowledge (p = 0.020), attitude (p = 0.012), economic status (p = 0.000), dietary restrictions (p = 0.000), and health worker counseling (p = 0.000). Conclusion: It is concluded that the application of balanced nutrition is influenced by factors such as knowledge, attitude, economic status, dietary restrictions, and counseling by health workers. Therefore, it is expected that pregnant women and families can allocate time to attend nutrition counseling provided by health workers to enhance maternal knowledge on how to address undernutrition issues, as well as regularly seek information on good nutrition for toddlers. Keywords: Balanced Nutrition Implementation, Under-Five Children